2018
DOI: 10.3389/fmicb.2017.02675
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Repertoire of Antibiotic Resistance Genes in Antibiotic Manufacturing Effluents and Receiving Freshwater Sediments

Abstract: Environments polluted by direct discharges of effluents from antibiotic manufacturing are important reservoirs for antibiotic resistance genes (ARGs), which could potentially be transferred to human pathogens. However, our knowledge about the identity and diversity of ARGs in such polluted environments remains limited. We applied functional metagenomics to explore the resistome of two Croatian antibiotic manufacturing effluents and sediments collected upstream of and at the effluent discharge sites. Metagenomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 72 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…This duplication represents an example of how bacteria can employ common stress response factors as antibiotic resistance genes. In addition, our work is now strengthened by two recently published studies where functional metagenomic databases constructed from antibiotic-rich environments pointed to hflX from Simkania negevensis and Emergencia timonensis as a putative resistance gene (23, 33). Based on our phylogenetic analysis, hflX from Eubacterium spp., which is closely related to E. timonensis , belongs to the hflXr family.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This duplication represents an example of how bacteria can employ common stress response factors as antibiotic resistance genes. In addition, our work is now strengthened by two recently published studies where functional metagenomic databases constructed from antibiotic-rich environments pointed to hflX from Simkania negevensis and Emergencia timonensis as a putative resistance gene (23, 33). Based on our phylogenetic analysis, hflX from Eubacterium spp., which is closely related to E. timonensis , belongs to the hflXr family.…”
Section: Discussionmentioning
confidence: 66%
“…However, a distinction should be made with hflXr , given that the tmRNA is a general stress factor, while hflXr duplication, specialization, and transcription regulation favor the idea that this gene is dedicated to response to antibiotics. In addition, functional metagenomic proves that hflX from other species that belong to the same subfamily as hflXr confer resistance to macrolides when transferred to other bacteria, which, to our knowledge, is not the case for tmRNA (23, 33). However, it has been shown that the sigma factor sigR induced by antibiotics in Streptomyces coelicolor regulates the transcription of various ribosome-associated genes, and notably tmRNA and HflX (36).…”
Section: Discussionmentioning
confidence: 78%
“…identify hflX homologs as putative antibiotic resistance genes belong to both the HflX-r (Emergencia spp) and HflX (Simkania spp.) clades (40,41). A possible explanation is that while all HflX proteins retain their ability to split 70S ribosomes into their subunits, their duplication allows each paralog to recognize ribosomes that are stalled under different physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the issue of pharmaceuticals in the environment has been gaining more attention worldwide and there has been growing interest in the WWTPs treating effluents from pharmaceutical industries with antimicrobial agents production. For example, several studies revealed the environmental impacts and the resistome of antimicrobial agents contaminated effluents from pharmaceutical industries in India and Croatia (Fick et al, 2009; Rutgersson et al, 2014; Bielen et al, 2017; Razavi et al, 2017; González-Plaza et al, 2018). A recent study in Nigeria has applied a culture-depend method to isolate ARB in wastewater from pharmaceutical facilities (Obayiuwana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%